The welfare impact of village fund allocation in Indonesia: The comparative of Java and Non-Java - Mardalena Mardalena; Ardi Adji; Siti Rohima; Harunurrasyid Harunurrasyid; Rahma Nida (Universitas Ahmad Dahlan, 2023)
There are inequality at the rural and urban levels that must be concern to the government. To reduce the inequality is to optimize village funds. Allocation of village funds is a stimulus to accelerate the village economy. Fiscal stimulus through village funds boost the economy at the village level. This research examines the impact of village fund allocation on economic performance in Java and non-Java. The Difference in Difference (DiD) method compares the average value of the observed variables before the village fund policy and the average variable value of development indicators and welfare indicators after the policy was implemented. The allocation of village fund has some good impacts on Indonesia's rural economy. We found that funding can boost welfare, such as improving clean water, per capita income, human development index, and reducing poverty. We also discovered that the Java area has a greater impact than the non-Java area. The results of this study provide essential information for formulating government plans and policies as a policy reference and evaluating the implementation of regional autonomy policies and allocation of village funds in Indonesia.